Estimates of the Long‐Run Growth Rate of Australia. Issue 1 (8th April 2013) - Shankar, Sriram; Bhaskara Rao, B.
<x xml:space="preserve">Abstract</x> This short note estimates using the Kmenta's (1967) approximation, a constant elasticity of substitution (CES) production function for Australia for 1960–2004. It is found that the elasticity of substitution is 2.44, technical progress is capital augmenting and the steady‐state growth rate (SSGR) of Australia is about 0.34%.